Case report: A novel mutation in TRPS1 identified in a Chinese family with tricho-rhino-phalangeal syndrome I: A therapeutic challenge - Huang, Qi; Jiang, Cheng; Sun, Jiazhong; Xue, Junli; Zhang, Victor Wei (Frontiers in Pediatrics, 2022)
Tricho-rhino-phalangeal syndrome (TRPS) is a rare autosomal dominant malformation caused by mutations involving the TRPS1 gene. Patients with TRPS exhibit distinctive craniofacial and skeletal abnormalities. This report presents three intra-familial cases with TRPS1 gene mutations that showed the characteristic features of TRPS. A 13-year-old boy was admitted to Department of Endocrinology for the evaluation of short stature. Physical examination revealed that the boy had thin sparse hair, pear-shaped nose, protruding ears, small jaw and brachydactyly. A survey of his family history indicated that the boy's sister and mother shared the same clinical features. Radiological techniques demonstrated a different degree of skeletal abnormalities in these siblings. Next-generation sequencing and quantitative PCR were performed and showed a novel deletion mutation in exons 3–5 in the three familial cases, confirming the diagnosis of TRPS I. The healthy father did not carry the deletion mutation. Currently, there was no specific therapy for TRPS I; however, genetic consultation may be useful for family planning